The role of multiple partners in a digestive mutualism with a protocarnivorous plant - Nishi, Aline Hiroko [UNESP]; Vasconcellos-Neto, João; Romero, Gustavo Quevedo (Oxford University Press (OUP), 2013)
Background and aimsThe protocarnivorous plant Paepalanthus bromelioides (Eriocaulaceae) is similar to bromeliads in that this plant has a rosette-like structure that allows rainwater to accumulate in leaf axils (i.e. phytotelmata). Although the rosettes of P. bromelioides are commonly inhabited by predators (e.g. spiders), their roots are wrapped by a cylindrical termite mound that grows beneath the rosette. In this study it is predicted that these plants can derive nutrients from recycling processes carried out by termites and from predation events that take place inside the rosette. It is also predicted that bacteria living in phytotelmata can accelerate nutrient cycling derived from predators.MethodsThe predictions were tested by surveying plants and animals, and also by performing field experiments in rocky fields from Serra do Cipó, Brazil, using natural abundance and enriched isotopes of 15N. Laboratory bioassays were also conducted to test proteolytic activities of bacteria from P. bromelioides rosettes.Key ResultsAnalyses of 15N in natural nitrogen abundances showed that the isotopic signature of P. bromelioides is similar to that of carnivorous plants and higher than that of non-carnivorous plants in the study area. Linear mixing models showed that predatory activities on the rosettes (i.e. spider faeces and prey carcass) resulted in overall nitrogen contributions of 26·5 % (a top-down flux). Although nitrogen flux was not detected from termites to plants via decomposition of labelled cardboard, the data on 15N in natural nitrogen abundance indicated that 67 % of nitrogen from P. bromelioides is derived from termites (a bottom-up flux). Bacteria did not affect nutrient cycling or nitrogen uptake from prey carcasses and spider faeces.ConclusionsThe results suggest that P. bromelioides derive nitrogen from associated predators and termites, despite differences in nitrogen cycling velocities, which seem to have been higher in nitrogen derived from predators (leaves) than from termites (roots). This is the first study that demonstrates partitioning effects from multiple partners in a digestion-based mutualism. Despite most of the nitrogen being absorbed through their roots (via termites), P. bromelioides has all the attributes necessary to be considered as a carnivorous plant in the context of digestive mutualism. © 2012 The Author. Published by Oxford University Press on behalf of the Annals of Botany Company. All rights reserved.
Keywords: Animal-plant interactions; carnivorous plants; digestive mutualisms; Isoptera; Latrodectus geometricus; multiple partners; nitrogen cycling; nutrient flux; Paepalanthus bromelioides; rupestrian fields; stable isotopes of 15N; nitrogen; bioaccumulation; bioassay; biological uptake; carnivorous plant; developmental biology; digestion; linearity; nitrogen isotope; nutrient cycling; plant-insect interaction; recycling; spider; stable isotope; termite; animal; Brazil; carnivory; Eriocaulaceae; metabolism; microbiology; physiology; plant leaf; predation; symbiosis; Tenebrio; Animals; Carnivory; Nitrogen; Nitrogen Isotopes; Plant Leaves; Predatory Behavior; Spiders; Symbiosis; Minas Gerais; Serra do Cipo; Serra do Espinhaco; Animalia; Araneae